A New Newton-Wavelet Algorithm to Solve Non-Linear Equations - Ibraheem, Kais; Abdullah, Riyad (AL-Rafidain journal of computer sciences and mathematics, 2006)
In this research, a new algorithm to solve the non-linear equations (f(x)=0) was developed. The new method was called Newton –Wavelet which can be defined as a mix between two methods, Newton and wavelet. By applying this algorithm on seven examples and compared the result with the Broyden method it has shown a good efficiency. The new method shows that it can decrease the number of iterations and then decrease the time needed to solve the used equations. This algorithms considered a new technique of mixes between two subjects the first one is a numerical analysis (by using Newton method) and the second is an image processing and data compression (by using Wavelet analysis), The basic aim of this research is decrease the time of solution.